Study of Doppler waveforms in pregnancy induced hypertension and its correlation with perinatal outcome - K, Smitha; K, Sowmya; T, Malathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objectives of current study were to study the significance of Doppler in PIH using middle cerebral artery and umbilical artery blood flow and to analyze the role of Doppler in PIH in predicting perinatal outcome. Methods: Hundred cases of women with pregnancy induced hypertension between 28-40 weeks of gestation were studied for umbilical artery and middle cerebral artery Doppler waveforms. The perinatal outcome results were documented and analyzed statistically using percentage and Chi-square test. Results: Adverse perinatal outcome was significantly associated with oligohydramnios (P <0.0001) and grade 3 placental maturity (P <0.01). Absent end diastolic flow waveform in umbilical artery was associated with mortality of 27.78% and reverse end diastolic waveform with mortality of 100%. UA PI has the highest sensitivity (88.88%) and positive predictive value (69.56%) in predicting low birth weight. Cerebroplacental ratio (MCA/UA) had highest sensitivity (94.42%), PPV (86.42%), accuracy (90%) for predicting adverse perinatal outcome than UAPI and MCA PI. MCA PI had low specificity in predicting adverse perinatal outcome. Conclusions: Pregnancy induced hypertension is associated with significant fetal morbidity and mortality. Oligohydramnios in PIH patients is associated with adverse pregnancy outcome. Presence of absent end diastolic flow and reversed end diastolic flow in umbilical artery is an ominous sign with high perinatal mortality. Reversed end diastolic flow is more ominous than absent end diastolic flow. Cerebroplacental ratio (MCA/UA PI) is a better predictor of adverse perinatal outcome, with highest diagnostic accuracy, sensitivity, and positive predictive value, than either vessel Doppler indices considered alone. Colour Doppler study is a simple, quick, non-invasive procedure and is found to be the most accurate among the other tests for antepartum fetal surveillance.